Massification, an intervening factor in Pichon-Riviere’s Theory of the Single Disease - Sánchez Jiménez, Hugo Manuel (2024)
This article aims to recognize the relationship between the behavior of mass society, called massification, with the notions of bond, role, and spokesperson; from the framework of Pichon-Rivière’s Theory of the Unique Illness. Seen in this way, the massification of society constitutes a phenomenon that encourages certain values and tendencies to expand until they take root in the psyche with Elective; since it is clear that, in the individual’s encounter with society, the latter establishes its particular rules and assigns roles that he mistakenly assumes in the bond he has with himself and with others. Thus, the effects of massification can be analyzed by various social disciplines, in this case, by psychology, since anomie and alienation maintain a close relationship in mass culture, phenomena that are taken into account in this paper. At the same time, it is unavoidable for us to include Freud’s significant contribution to the dynamics of the idealization of the leader in a mass, a problematic and palpable situation because it is part of the outcome of the anomic processes of today’s society. Some empirical evidence is alsopresented to support the theoretical framework: on the relationship between linkage and illness and on the consequences of overcrowding. At the same time, the studies indicate that, apparently, the passage of COVID 19 aggravated living conditions in genera.